Determinants of Firm Value with Enterprise Risk Management as a Moderating Variable in KBMI 3 and 4 Commercial Banks - Melati, Rampi; Siswati, Indra (International Journal Labs, 2025)
The banking sector plays a pivotal role in a nation's economic stability and growth, with firm value being a critical indicator of a bank's health and market perception. In Indonesia, banks are categorized based on core capital (Kelompok Bank Berdasarkan Modal Inti—KBMI), where groups 3 and 4 comprise the largest institutions with significant systemic influence. This research aims to analyze the influence of profitability, credit risk, institutional ownership, and corporate social responsibility (CSR) on firm value, with enterprise risk management (ERM) as a moderating variable. Firm value is measured using the Price to Book Value (PBV) ratio. The sample consists of 13 commercial banks categorized under KBMI 3 and 4 during the period 2017 to 2024. The analytical method used is Moderated Regression Analysis (MRA) with a fixed effect model approach. The results indicate that Profitability has a positive effect on Firm Value, while Credit Risk has a negative effect. In contrast, Institutional Ownership and Corporate Social Responsibility show no significant effect. The moderation test further reveals that Enterprise Risk Management weakens the relationship between Institutional Ownership and Firm Value but does not moderate the effects of Profitability, Credit Risk, and Corporate Social Responsibility on Firm Value.